Propuestas didácticas mediadas por tecnologías digitales para el desarrollo de competencias de lectura y escritura académicas - Álvarez, Guadalupe (Universidad de San Buenaventura - Cali, 2017)
As part of an investigation which is aimed at characterizing and understanding practices of teaching writing with digital technologies in the middle and upper level in Argentina, this paper describes and analyzes two educational experiences (on Facebook and Moodle, respectively) which have been designed to develop academic reading and writing skills by using different tools and devices that integrate new technologies. !e case analysis is performed taking into account four basic dimensions: 1) the criteria by which the experiences were planned and designed; 2) different modalities of implementation; 3) the characteristics adopted in reformulation exercises on the wall and Moodle, respectively; 4) the point of view of students on such spaces. Even when experiences are preliminary analysis, they provides tools to rethink teaching strategies in order to integrate digital technologies in teaching and learning proposals aimed at improving academic literacy.